ChemInform Abstract: Carbon—Carbon Bond Cleavage Reaction: Synthesis of Multisubstituted Pyrazolo[1, 5‐a]pyrimidines. Issue 45 (November 2015) - Saikia, Pallabi; Gogoi, Sanjib; Boruah, Romesh C
Abstract A base‐induced cyclization of 1, 3, 5‐triphenylpentane‐1, 5‐diones and 3‐pyrazolamines affords 5, 7‐diphenylpyrazolo[1, 5‐a]pyrimidines in good yields via C—C bond cleavage.